Potentials of SGLT2 inhibitors in the treatment of diabetic rotator cuff diseases: a comprehensive review - Morya, Vivek Kumar; Lang, Jun; Kwak, Mi-Kyung; Noh, Kyu-Cheol (Clinics in Shoulder and Elbow, 2025)
Degenerative rotator cuff disease (RCD) is a common musculoskeletal condition that disproportionately affects individuals with diabetes mellitus, leading to pain, functional impairment, and a reduced quality of life. Emerging evidence suggests that sodium-glucose co-transporter 2 inhibitors (SGLT2is), which are widely used for glycemic control in type 2 diabetes, offer additional musculoskeletal benefits beyond their metabolic effects. This review explores the potential protective role of SGLT2is in diabetic RCD by examining the epidemiological link between diabetes and tendon degeneration and evaluating the biological mechanisms through which SGLT2 is influence tendon health. These potential benefits include reducing inflammation, altering metabolism to a more tendon-friendly state, combating oxidative stress with ketones, encouraging a healing environment through macrophage modulation, and improving overall health via weight and blood sugar management. Preclinical and observational studies provide preliminary support for therapeutic benefits, although high-quality randomized clinical trials are lacking. Understanding the multifaceted role of SGLT2is in tendon biology will open new avenues for prevention and management of RCD, particularly in patients with metabolic disorders.